2007
DOI: 10.1007/s10719-007-9056-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oligosaccharide fragments corresponding to the exopolysaccharide released by Streptococcus macedonicus Sc 136

Abstract: Hexa-, penta- and tetrasaccharide fragments related to the repeating unit of the exopolysaccharide secreted by Streptococcus macedonicus Sc 136 were synthesized in a very efficient manner involving minimum number of steps. A general glycosylation condition has been applied for all glycosylation steps and yields were excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The target tetrasaccharide as its p -methoxyphenyl (PMP) glycoside was synthesized following a sequential glycosylation approach from the suitably functionalized monosaccharide intermediates 2 [13], 3 [14], 4 [15] and 5 [16]. These monosaccharide intermediates were prepared from the commercially available reducing sugars by using a number of recently developed reaction conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The target tetrasaccharide as its p -methoxyphenyl (PMP) glycoside was synthesized following a sequential glycosylation approach from the suitably functionalized monosaccharide intermediates 2 [13], 3 [14], 4 [15] and 5 [16]. These monosaccharide intermediates were prepared from the commercially available reducing sugars by using a number of recently developed reaction conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of four amino sugars and, more precisely, three α-linked 2-acetamido-2-deoxy- d -galactose moieties makes the synthesis challenging due to difficulties associated with the construction of 1,2- cis glycosidic linkages. 18 Retrosynthetic analysis (Figure 1 ) revealed that the desired pentasaccharide 1 could be synthesized using a number of suitably protected monosaccharide intermediates 2 , 19 3 , 20 4 21 and 5 , 22 which can be prepared from commercially available monosaccharides using reported reaction conditions. In order to achieve 1,2- cis glycosidic linkages, d -galactose-derived 2-azido-2-deoxy- d -galactose thioglycoside intermediate 4 was used twice in the synthetic strategy for the installation of α-linked 2-acetamido-2-deoxy- d -galactose moieties in compound 1 .…”
mentioning
confidence: 99%
“…Selective acetylation of compound 6 via an orthoester formation furnished monosaccharide acceptor 7 in 75% yield. Ethyl 2,3,5,6-tetra-O-benzoyl-1-thio-α-D-galactofuranoside (10) [23,24] was prepared from D-galactose following the reported literature. Compound 13 [25] was prepared from commercially available N-acetylneuraminic acid following a threestep reaction sequence consisting of methyl ester formation, acetylation and thioglycosidation.…”
mentioning
confidence: 99%